A importância da gestão estratégica em cartórios judiciais: alguns elementos de análises do funcionamento de cartórios judiciais cíveis de comarcas de 3ª entrância do Tribunal de Justiça do estado do Tocantins - Rocha, Vânia Ferreira da Silva (Universidade Federal do Tocantins, 2018)
The slowness of the Brazilian justice and the causes related to delayed jurisdictional provision have become one of the major challenges of the Judiciary which, for a long time has been considered inefficient by its way of acting in the resolution of the conflicts. Mechanisms aimed at improvement the quality of the rendered services to the besides reorganizing the internal structure of the Judiciary are seen by the National Council of Justice, as the management and planning body of the national judiciary, as the main instruments to alleviate this problem. In this sense, the Courts of Justice of the whole country were called to align themselves up to the macro-challenges of the National Judicial Power. With this objective, the judiciary the state of Tocantins, through its Strategic Planning, defined its mission which is to be among the best Courts of Justice and be recognized as more modern, swift and effective until 2020. And formulated objectives and challenges to be followed by all who integrate it. In this sense, to know how the members of the judiciary of Tocantins are working and the way that the procedures are done it becomes fundamental for a concrete analysis about its contributions to the achievement of the institutional objectives and mission of the Judiciary Power of the State of Tocantins which is to be among the best Courts of Justice and recognized as being more modern, faster and 2020. From this perspective and considering that the first instance directly exercises the final activity of the Judiciary this study delimited to analyze some of the management procedures and management routines adopted by the Judicial Courts of input of 3rd input of Justice of the State of Tocantins identifying the main obstacles considered responsible for the morosity of justice. In addition to verifying how the clerk practices at first instance may interfere with the final results provided in the Justice Report in Numbers prepared by the National Council of Justice. For this purpose, bibliographic research was done on the subject as well as an analysis of the regulations in TJTO to the first degree of jurisdiction. In addition, a chapter was designed for a comparative study between two Civil Judicial Offices of third-order input of the TJTO, where their profiles were described, as well as the results found. As a final product, some actions considered fundamental for the improvement of services rendered and effectiveness of justice were proposed.